Characteristics and Outcomes of Discharge Against Medical Advice and 30-Day Readmissions After Concussion: Analysis of the Nationwide Readmissions Database. Issue 3 (24th September 2022) - Jumah, Fareed; Chotai, Silky; Hilden, Patrick; Raju, Bharath; Nagaraj, Anmol; Agarwalla, Pankaj; Johnson, Stephen; Gupta, Gaurav; Sun, Hai; Nanda, Anil
Abstract : BACKGROUND: Little is known about the impact of discharge against medical advice (DAMA) in patients admitted with concussion. OBJECTIVE: To explore the prevalence of DAMA and its effect on 30-day readmissions and cost in concussion using a nationally representative sample. METHODS: The Nationwide Readmissions Database was queried for concussion admissions and their disposition at discharge between 2010 and 2014. Included patients were ≥18 years old who were admitted with concussion and had <1 hour loss of consciousness. We excluded in-hospital deaths or discharge dispositions other than home or against medical advice. Univariate and multivariate analyses were performed to determine characteristics associated with DAMA and 30-day readmissions. RESULTS: A total of 38 919 index admissions were identified, which resulted in 998 (2.6%) DAMA. In multivariate analysis, characteristics associated with DAMA included younger age (odds ratio [OR] = 0.84, 95% CI 0.80-0.88), male sex (1.47, 1.22-1.76), an Elixhauser comorbidity index >3 (1.67, 1.15-1.60), and assault (2.02, 1.48-2.75) and fall injuries (1.28, 1.03-1.60). The highest-income quartile was negatively associated with DAMA (0.91, 0.73-1.13). In multivariate analysis, DAMA (1.63, 1.29-2.06), higher comorbidity index (2.61, 2.22-3.06), and self-inflicted mode of injury (2.28, 1.30-4.02) were independently associated with 30-day readmission. The most common indication for readmission in both routine and DAMA groups was traumatic injury (21.1% and 24.5%, respectively). CONCLUSION: DAMA is an independent risk factor for readmission in patients admitted for concussion. The variables associated with DAMA identified in this study can be used to design patient-centered interventions that can be implemented to reduce DAMA and its impact on clinical outcomes in patients with traumatic brain injury.